Engineering efficient bifunctional electrocatalysts for rechargeable zinc–air batteries by confining Fe–Co–Ni nanoalloys in nitrogen-doped carbon nanotube@nanosheet frameworks. Issue 48 (7th December 2020) - Tang, Xiannong; Cao, Rui; Li, Longbin; Huang, Bingyu; Zhai, Weijuan; Yuan, Kai; Chen, Yiwang
Abstract : Fe–Co–Ni nanoalloys embedded in nitrogen-doped carbon nanotube@nanosheet frameworks (FeCoNi-NC) is prepared as excellent bifunctional ORR/OER electrocatalyst, which is confirmed by experimental observations and theoretical calculations. Abstract : Developing precious-metal-free bifunctional oxygen reduction and evolution reaction (ORR/OER) electrocatalysts is of great significance for several key energy conversion and storage systems, yet remains a formidable challenge. Herein, we systematically designed Fe–Co–Ni trimetallic nanoalloys encapsulated in nitrogen-doped carbon nanotube@nanosheet frameworks (FeCoNi-NC) for application as effective bifunctional ORR/OER electrocatalysts. The rational structural design of FeCoNi-NC provides hierarchical porosity coupled with greatly increased effective electrochemical specific area for exposing abundant active sites and enhanced mass-transfer capability toward the ORR/OER. Experimental observations and theoretical calculations confirmed that Fe–Co–Ni nanoalloys interacting with pyridinic nitrogen-rich carbon synergistically optimized the adsorption/desorption free energies of oxygen intermediates, thus significantly enhancing the intrinsic ORR/OER activity. Consequently, FeCoNi-NC exhibits remarkable bifunctionality for the ORR (half-wave potential of 0.89 V) and OER (1.54 V at 10 mA cm −2 ) with Δ E = 0.65 V, and even outperforms Pt/C–RuO2 benchmarks. Moreover, the corresponding zinc–air battery shows large power density (315.2 mW cm −2 ), high capacity (803.78 mA h g −1 at 100 mA cm −2 ) and excellent cycling durability (over 100 hours at 50 mA cm −2 ), further testifying its practical applications. This work demonstrates an effective pathway to highly active non-precious-metal bifunctional catalysts toward sustainable energy technologies.